2015
DOI: 10.1103/physrevb.92.125103
|View full text |Cite
|
Sign up to set email alerts
|

Shear viscosity of strongly interacting fermionic quantum fluids

Abstract: Eighty years ago, Eyring proposed that the shear viscosity of a liquid η has a quantum limit η n where n is the density of the fluid. Using holographic duality and the anti-de Sitter/conformal field theory correspondence in string theory, Kovtun, Son, and Starinets (KSS) conjectured a universal bound η s 4πk B for the ratio between the shear viscosity and the entropy density s. Using dynamical mean-field theory, we calculate the shear viscosity and entropy density for a fermionic fluid described by a single-ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…equation for a sound wave propagating at velocity c 1 which is in agreement with our analysis and interpretation of equation(20).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…equation for a sound wave propagating at velocity c 1 which is in agreement with our analysis and interpretation of equation(20).…”
supporting
confidence: 89%
“…To better understand η/s within the context of strongly correlated systems, we develop a simple theoretical model to calculate the quasiparticle scattering rates of a strongly correlated quantum liquid above T c . Such a model differs from past calculations [17][18][19][20] in that we include the effects of superfluid fluctuations as T T c  + .…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, based on the dynamical mean field theory (DMFT), Pakhira and McKenzie have found that both the KSS and Hartnoll bounds are violated in a singleband Hubbard model [7,8]. For the shear viscosity to entropy density ratio for an electron fluid, which is described by a single-band Hubbard model at half filling, the KSS bound was found to be strongly violated in the bad-metal regime for parameters appropriate to lattice electronic systems, such as cuprates and organic charge-transfer salts.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, an arbitrary violation of the KSS bound would occur if H(u H ) → ∞, so a specific C cannot exist. In turn, D would also break down [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Here, l ee = 2 kF EF kT 2 is the mean free path of e-e scattering, k F = mV F /h the Fermi vector. At T = 0 the e-e collisions are completely damped, then l η = a while electron viscosity yields a constant value η = 1 5 h m [21]. Then, at finite temperature viscosity length scale is defined mostly by scattering with atomic core while l η ≤ a.…”
Section: Pacs Numbersmentioning
confidence: 98%